1996
DOI: 10.1093/nar/24.24.4895
|View full text |Cite
|
Sign up to set email alerts
|

Two Different RNA Binding Activities for the AU-Rich Element and the Poly(A) Sequence of the Mouse Neuronal Protein mHuC

Abstract: HuC is one of the RNA binding proteins which are suggested to play important roles in neuronal differentiation and maintenance. We cloned and sequenced cDNAs encoding a mouse protein which is homologous to human HuC (hHuC). The longest cDNA encodes a 367 amino acid protein with three RNA recognition motifs (RRMs) and displays 96% identity to hHuC. Northern blot analysis showed that two different mRNAs, of 5.3 and 4.3 kb, for mouse HuC (mHuC) are expressed specifically in brain tissue. Comparison of cDNA sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
90
2
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(102 citation statements)
references
References 61 publications
7
90
2
3
Order By: Relevance
“…Previous studies showed that RRM1 and RRM2 are sufficient for binding to the ARE (35,36), whereas RRM3 is capable of binding to poly(A) in a filter binding assay (37). By deletion mutant analysis, it has been shown that RRM3 of HuR is necessary for stabilization (21) and that the hinge region contains the nucleocytoplasmic shuttling signal (38).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that RRM1 and RRM2 are sufficient for binding to the ARE (35,36), whereas RRM3 is capable of binding to poly(A) in a filter binding assay (37). By deletion mutant analysis, it has been shown that RRM3 of HuR is necessary for stabilization (21) and that the hinge region contains the nucleocytoplasmic shuttling signal (38).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro selection had previously been carried out for HuB and HuC (19,26,56). Three rounds of binding selection with HuB, using an RNA carrying a randomized region of 25 nucleotides, had yielded predominantly RNAs that contained U 3-5 -tracts (19) and binding selection using a 3ЈUTR library had selected RNAs that contained the sequence Pu(U/A)U 3 AU 3 (U/A)Pu (where Pu indicates a purine) (56).…”
Section: Figmentioning
confidence: 99%
“…Three rounds of binding selection with HuB, using an RNA carrying a randomized region of 25 nucleotides, had yielded predominantly RNAs that contained U 3-5 -tracts (19) and binding selection using a 3ЈUTR library had selected RNAs that contained the sequence Pu(U/A)U 3 AU 3 (U/A)Pu (where Pu indicates a purine) (56). A similar iterative selection of HuC-binding RNAs indicated that HuC binds to RNAs carrying the sequence Pu(U) 2-5 (Pu) 1-2 (U) [2][3][4][5] Pu (26).…”
Section: Figmentioning
confidence: 99%
“…3). Previous in vitro studies on Hu proteins have shown that RBDs 1 and 3 are required for binding to AREs and the poly(A) tail, respectively (Abe et al 1996b;Chung et al 1996;Ma et al 1997). Therefore, the binding of HuD to some speci®c ARE-containing mRNAs and also possibly the export of the mRNAs to the cytoplasm by shuttling may be involved in the induction of neurite outgrowth.…”
Section: The Novel Nes Of Hud and The Nucleocytoplasmic Shuttling Of mentioning
confidence: 99%